Utilizing waste cast stone: compression strength analysis and implication for suitable cast stone production - Mudgal, Devanshu; Pagone, Emanuele; Salonitis, Konstantinos (Springer, 2024)
In recent years, the concept of circular economy has become increasingly popular as a sustainable approach to resource management. The present study explores the potential of reusing cast stone waste generated during the production process, in alignment with the principles of the circular economy. Cast stone waste typically goes to landfill sites discarded as a byproduct and poses environmental challenges due to its non-biodegradable nature. This work focuses on reusing this waste material as a viable resource, thus mitigating the environmental impact. Through a series of compression test experiments on cast stone, the presented study investigates the effectiveness of incorporating cast stone waste into production. The findings of this study contribute to cost reduction in raw material and waste minimization promoting economic and environmental benefits.
Keywords: Uniaxial compression test; Cast stone; Recycled aggregates